A SYSTEMATIC REVIEW OF THE EVALUATION OF NEONATAL SEPSIS DIAGNOSIS USING INTERLEUKINS - Adrianne, Samantha (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Aim: This study aims to summarize and evaluate the diagnostic potential and accuracy of interleukins (ILs) level as a diagnostic marker for neonatal sepsis. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded. Results: Database searches identified a total of 19553 articles. Of these, 100 articles passed the screening process, resulting in 20 articles for full-text assessment. Among them, 11 articles did not evaluate the outcome of interest. Hence, we found 9 appropriate studies included. The ILs reported include IL-6, IL-10, IL-18, and IL-27, with the most common reported was IL-6. Conclusion: Current evidences supports the potential predictive utility of ILs level, especially IL-6, as a potential diagnostic marker for detecting neonatal sepsis. To determine the precise predictive efficacy of the marker, well-designed prospective studies had to be conducted due to the methodological variability and variation of the implemented thresholds.